Estimation rumen degradable protein of local feeds in dairy cattle using in sacco method. Issue 1 (October 2021) - Rosmalia, A; Permana, I G; Despal; Zahera, R
Abstract: There is a lack of nutrition information on local feeds protein in Indonesia, especially to determine protein fraction of dairy feed. The objective of this study was to determine rumen degradable protein (RDP) of local feeds in dairy cattle using in sacco method. The local feeds are copra meal, palm kernel meal, coffee husk, tofu waste, soy-sauce waste, brewer waste, and habbatussauda waste. Two ruminal fistulated male Frisian Holstein were used to determine rumen degradable protein using in sacco method. The parameters observed include the estimated kinetic parameters, effective degradability (ED), and RDP. The parameters were evaluated with analysis of variance using SAS University software. The result showed that tofu waste and habbatussauda waste had high potential rapid degradation of CP following by brewer waste, palm kernel waste, soy-sauce waste, copra meal, and coffee husk. Habbatussauda waste had higher RDP followed by brewer waste, tofu waste, copra meal, palm kernel meal, soy-sauce waste, and coffee husk. There was a positive correlation between RDP and crude protein content, and a negative correlation between RDP and crude fiber. It is concluded that local feeds have various characteristics of quality feed protein, which is shown by rumen degradable protein and rumen undegradable protein.